Sound Change of Modern Standard Arabic Sudanese of Khartoum and Chadian Dialect - Suparno, Darsita; Satori, Achmad; Zakaria, Muhammad Fadhlurrahman; Nurhuda, Zamzam; Chairul, Akbar Amanah Illahi; Zekyzak, Fathalla Mohammed Fathalla (Arabi : Journal of Arabic Studies, 2025)
This article discusses sound change and sound correspondence in Modern Standard Arabic (MSA), Sudanese Khartoum Arabic Dialect (SAKD), and Chadian Sudanese Arabic Dialect (SACD). The focus is on the relationship between form and meaning as seen in cognates and the alternation between strong and weak sonorants through lenition and fortition. It also highlights phonological processes such as apheresis, apocope, and syncope within the syllable structure of each variety. This study addresses a gap in comparative Arabic dialect phonology. Data were obtained from one Sudanese and two Indonesian students. The analysis follows Crowley’s theory using a qualitative-descriptive approach. The main data source is 207 basic words from Swadesh’s list. The results show 16 cognates, 190 word-pairs with phonemic variation, and several cases of sound change. These findings are spread across various word classes, including nouns, verbs, adjectives, pronouns, and adverbs, illustrating the rich diversity within Arabic dialectal phonology in Semitic linguistic evolution.